Rudolph's pediatrics - Kline, Mark W. (McGraw-Hill Education, 2018)
Presented in full color, the Twenty-Third Edition provides an up-to-date, in-depth survey of pediatric medicine unmatched by any other text. With its algorithmic approach to pediatric systems, the book facilitates the diagnosis and treatment of both common and uncommon pediatric illnesses; and it reflects new technologies and advances in molecular medicine that continue to evolve with current thinking about normal childhood development and pediatric disease processes.